Reformulasi Regulasi Transisi Energi Dalam Mewujudkan Target Nationally Determined Contribution Guna Memenuhi Target Low Emission (RechtJiva, 2025)
The Paris Agreement is an international treaty aimed at protecting the environment at both national and global levels by reducing the use of non-renewable energy and replacing it with renewable energy sources that efficiently minimise carbon emissions in the atmosphere. The framework of this agreement emphasises limiting global warming to below 2°C, with efforts to further restrict it to 1.5°C. To achieve this, each country is required to develop strategies for implementing its commitments, which are outlined in the Nationally Determined Contributions (NDC) as a guiding document for energy transition policies. Sweden, as a comparative country in this study, has not only implemented climate regulations but also adopted a strategy incorporating the energy trilemma concept, which balances fairness, security, and sustainability. This approach has positioned Sweden as a leading country in terms of energy system performance and preparedness. This research aims to analyze the regulatory framework of energy transition in achieving the Nationally Determined Contribution (NDC) targets toward a low-emission future in Indonesia, and to explore and formulate an ideal regulatory model for energy transition to support the attainment of these targets. In contrast, Indonesia needs establish more explicit climate-related regulations similar to those in Sweden to enhance its energy transition efforts. This study employs a juridical research method, using statutory, comparative, and conceptual approaches. The research findings lead to recommendations for reformulating policies into a comprehensive climate change regulation in Indonesia. This proposed regulation should incorporate the energy trilemma concept and include essential components such as general provisions, objectives, the scope of climate change policies, implementation plans, governance frameworks, steering committees and responsible institutions, public participation, monitoring and evaluation mechanisms, and enforcement measures. By establishing a structured legal framework, Indonesia can developan effective and enforceable climate change policy that supports its energy transition goals.